2021
DOI: 10.1111/febs.15815
|View full text |Cite
|
Sign up to set email alerts
|

New targets for drug design: importance of nsp14/nsp10 complex formation for the 3’‐5’ exoribonucleolytic activity on SARS‐CoV‐2

Abstract: SARS‐CoV‐2 virus has triggered a global pandemic with devastating consequences. The understanding of fundamental aspects of this virus is of extreme importance. In this work, we studied the viral ribonuclease nsp14, one of the most interferon antagonists from SARS‐CoV‐2. Nsp14 is a multifunctional protein with two distinct activities, an N‐terminal 3’‐to‐5’ exoribonuclease (ExoN) and a C‐terminal N7‐methyltransferase (N7‐MTase), both critical for coronaviruses life cycle, indicating nsp14 as a prominent target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 57 publications
5
54
0
Order By: Relevance
“…The nsp14 exonuclease requires divalent cations like Mg 2+ , Mn 2+ , Ca 2+ , Ni 2+ , Cu 2+ , Co 2+ , or Zn 2+ for inducing structural changes and reaction activity. 16 , 17 The proofreading activity of nsp14 was associated with nsp10, and this activity could be hindered by sofosbuvir. 18 …”
Section: Introductionmentioning
confidence: 99%
“…The nsp14 exonuclease requires divalent cations like Mg 2+ , Mn 2+ , Ca 2+ , Ni 2+ , Cu 2+ , Co 2+ , or Zn 2+ for inducing structural changes and reaction activity. 16 , 17 The proofreading activity of nsp14 was associated with nsp10, and this activity could be hindered by sofosbuvir. 18 …”
Section: Introductionmentioning
confidence: 99%
“…While we still lack structural data for the SARS-CoV-2 full-length nsp14-nsp10 complex, the structure for its SARS homologue has been previously determined 3,4 confirming this type of arrangement deduced by our MST data in which only the ExoN domain but not the N7-MTase domain is involved in binding to nsp10. Owing to the very high protein sequence identify between SARS and SARS-CoV-2 nsp14 18 , we hypothesise that the SARS-CoV-2 nsp14-nsp10 complex displays the same characteristics as observed for the SARS complex and that the affinity is relatively weak with K d values in the low micromolar range. To the best of our knowledge, the work shown here is the first time the quantitative interaction between the two proteins is reported for coronaviruses.…”
Section: Sars-cov-2 Nsp14 and Nsp10 Form A Weak Affinity Complexmentioning
confidence: 90%
“…Finally, we also tested for a potential interaction between the nsp14 N7-MTase domain and nsp10, but did not observe any interacting between these two proteins under similar experimental conditions (Figure 4C) thereby also excluding any artefacts due to the presence of the N-terminal tag. Recently we became aware of work showing the interaction of nsp10 and nsp14 from SARS-CoV-2 using SPR 18 . While the authors show an interaction between these two proteins, steady-state analysis of interaction curves did not allow to unambiguously quantify K d values for the interaction from these experiments 18 .…”
Section: Sars-cov-2 Nsp14 and Nsp10 Form A Weak Affinity Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, Saramago et al . [ 10 ] performed an elegant biochemical characterisation of the SARS‐CoV‐2 nsp14/nsp10 complex. They demonstrated that complex formation is a critical requirement for optimal nsp14 exoribonuclease activity, which is, in turn, essential for completion of the viral life cycle.…”
mentioning
confidence: 99%